Strength-thermal conductivity synergy of aluminum alloys revealed by Al–RE (RE = Ce, La, Gd, Y, Sm, Yb, Er) intermetallic compounds - Wen-jing Liu; Yuan-dong Li; Jin Qiu; Xiao-mei Luo; Hong-wei Zhou; Guang-li Bi; Ti-jun Chen (Materials & Design)
Achieving both high strength and thermal conductivity in Al alloys is crucial but challenging. Although adding rare-earth (RE) elements can enhance mechanical properties, the effects on the synergy between thermal conductivity and mechanical properties of Al–RE alloys remain unclear. Herein, Al alloys with 1–5 wt% RE (Ce, La, Gd, Y, Sm, Yb, and Er) were prepared using permanent mold casting to investigate microstructural evolution and the synergistic relationship between thermal conductivity and mechanical properties. The result reveal that RE elements refined the α-Al phase, enhanced grain roundness, and promoted the formation of intermetallic compounds such as Al11Ce3, Al11La3, Al3Gd, Al3Y, Al4Sm, Al3Yb, and Al3Er. First-principles calculations demonstrated that Al3Gd, Al3Yb, and Al3Er exhibit brittleness, whereas other Al–RE intermetallic compounds displayed ductility. All identified intermetallic compounds exhibited metallic characteristics with significantly lower thermal conductivities than the Al matrix. Experimental results indicate that the thermal conductivity was negatively correlated with mechanical strength in Al–RE alloys but positively correlated with elongation. The traditional effective medium theory was optimized using a multi-physics coupled framework, enabling highly accurate prediction of the thermal conductivity in alloy systems. These findings offer insights to designing Al alloys with balanced strength and thermal conductivity.